The Role of Digital Tools in Enhancing Creative Thinking in Visual Arts Education - Olimova Mohidil Sherzod qizi, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article examines the impact of digital tools on fostering creative thinking in visual arts education. It explores how multimedia applications, interactive platforms, and animation software can improve students’ artistic skills, visual literacy, and creative problem-solving abilities. The study discusses pedagogical strategies, including project-based learning and flipped classrooms, to integrate digital tools effectively. Findings indicate that technology-enhanced visual arts instruction increases engagement, motivation, and collaboration while supporting individual learning needs.